PROFIL KEPERCAYAAN DIRI SISWA DI SMK KIMIA DHARMA BHAKTI - Cici Ambar Wati; Ecep Supriatna (IKIP Siliwangi, 2023)
The purpose in this study to find out the picture of student confidence in SmK Kimia Dharma Bhakti, Confidence becomes a very important factor in the development of students in school in this study using many aspects of self-confidence including objectivist, optimistic, responsible, realistic and rational. The methods in this study use quantitative deriftive methods. Participants in this study were students at SmK Kimia Dharma Bhakti as many as 99 people. The procedure in data collection uses a confidence questionnaire of 40 questions. The research conducted showed that the confidence of students in SmK Kimia Dharma Bhakti was as many as 75 students with a percentage of 76% in the moderate category while based on the category of the more dominant aspect of self-confidence there were in the rational aspect, namely 71 students with a percentage of 72%.Keywords: Selfconfidence, SMKKimia Dharma Bhakti